Proximate and mineral composition of venezuelan cocoa beans from Cata and Cuyagua - Lanza, José (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
Venezuelan cocoa is renowned for its high sensory quality; however, the presence of heavy metals may restrict its access to highly regulated international markets such as the European Union. This study aimed to evaluate the proximate composition and mineral content of cocoa beans (Theobroma cacao L.) collected from Cata and Cuyagua (Aragua, Venezuela) during the main harvest seasons of 2013 and 2014. Thirty samples (15 per year) were analyzed. Proximate composition was determined using official AOAC methods, while mineral elements were quantified following microwave-assisted acid digestion and ICP- OES analysis. Results showed that moisture content was significantly higher in 2013 compared to 2014 (p<0.001), whereas fat, protein, ash, and carbohydrate contents did not differ between years. Significant interannual differences were observed in mineral composition, with higher concentrations of Ca, Cu, Fe, Mg, and Mn in 2013, and increased levels of K and Na in 2014. Cadmium exhibited a non-significant decrease between years (1.62 - 1.04 mg.kg-1), while chromium remained low and stable. Arsenic and mercury were detected only at trace levels, with no significant differences between years. These results provide reference values for cocoa produced in Cata and Cuyagua, confirm interannual variability in proximate and mineral composition, and emphasize the importance of continuous monitoring of cadmium and other metals to ensure compliance with international regulations.